Excessive use of social media by high school students in southern Brazil - Yohana Pereira Vieira; Vanise dos Santos Ferreira Viero; Elizabet Saes-Silva; Priscila Arruda da Silva; Laura Silva da Silva; Mirelle de Oliveira Saes; Lauro Miranda Demenech; Samuel Carvalho Dumith (Sociedade de Pediatria de São Paulo, 2022)
Abstract Objective: To assess the prevalence of excessive use of social media and associated factors, as well as possible health consequences in high school students in southern Brazil. Methods: This is a population-based cross-sectional study, conducted with high school students in the city of Rio Grande, RS. All students who were attending high school at the Federal Institute of Rio Grande do Sul, campus Rio Grande, were eligible for this research in the second semester of 2019. In total, 513 students participated in the study. The dependent variable was excessive use of social media, defined as more than five hours per day. Descriptive and bivariate analyses were carried out and the Poisson regression was used to verify associations, with robust adjustment of variance. Results: The prevalence of students who reported excessive use of social media was 35.9%. The groups that were most susceptible to excessive use of social media had the following profile: female, black/brown skin, aged between 18 and 20 years old, attending the first year of high school. Excessive use of social media was shown to be associated with smoking, risk of depression, anxiety and stress, high risk of suicide and drug use. Conclusions: More than a third of students used social media excessively. This behavior was associated with negative health outcomes.